2014
DOI: 10.1104/pp.114.245027
|View full text |Cite
|
Sign up to set email alerts
|

Automated Update, Revision, and Quality Control of the Maize Genome Annotations Using MAKER-P Improves the B73 RefGen_v3 Gene Models and Identifies New Genes  

Abstract: The large size and relative complexity of many plant genomes make creation, quality control, and dissemination of high-quality gene structure annotations challenging. In response, we have developed MAKER-P, a fast and easy-to-use genome annotation engine for plants. Here, we report the use of MAKER-P to update and revise the maize (Zea mays) B73 RefGen_v3 annotation build (5b+) in less than 3 h using the iPlant Cyberinfrastructure. MAKER-P identified and annotated 4,466 additional, wellsupported protein-coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 48 publications
1
56
0
1
Order By: Relevance
“…In total, we identified 40,557 high-quality gene models in PH207 supported by aligned transcript evidence, protein evidence, or the presence of a Pfam domain (Finn et al, 2014). These gene models were distributed throughout the genome ( Figure 1B) in a distribution similar to that observed in the B73 reference genome assembly (Schnable and Ware et al, 2009;Law et al, 2015). The annotation edit distance analysis of the predicted gene set indicated that the gene annotations were generally well supported (Supplemental Figure 3) (Eilbeck et al, 2009;Yandell and Ence, 2012).…”
Section: Gene Annotation Of the Ph207 Genomementioning
confidence: 71%
See 1 more Smart Citation
“…In total, we identified 40,557 high-quality gene models in PH207 supported by aligned transcript evidence, protein evidence, or the presence of a Pfam domain (Finn et al, 2014). These gene models were distributed throughout the genome ( Figure 1B) in a distribution similar to that observed in the B73 reference genome assembly (Schnable and Ware et al, 2009;Law et al, 2015). The annotation edit distance analysis of the predicted gene set indicated that the gene annotations were generally well supported (Supplemental Figure 3) (Eilbeck et al, 2009;Yandell and Ence, 2012).…”
Section: Gene Annotation Of the Ph207 Genomementioning
confidence: 71%
“…The MAKER genome annotation pipeline was used to generate gene annotations (Campbell et al, 2014a(Campbell et al, , 2014bLaw et al, 2015). The PH207 genome assembly was first masked using RepeatMasker (http://www.…”
Section: Gene Model Structural Annotationmentioning
confidence: 99%
“…When including gene fragments without disabling mutations in a broader pseudogene definition, the total number of pseudogenes reached 267,546 in the Ae. tauschii genome, which is two times larger than the number in the maize genome (B73 RefGen_v3, in the 5b + annotation build) 21 . Therefore, Ae.…”
Section: Resultsmentioning
confidence: 99%
“…The scripts, parameters, and intermediate files of each transposable element superfamily are available at https://github.com/mcstitzer/maize_v4_TE_annotation. The MAKER P pipeline was used to annotate protein coding genes 46 , integrat ing ab initio prediction with publicly available evidence from full length cDNA 47 , de novo assembled transcripts from short read mRNA sequencing (mRNA seq) 48 , isoform sequencing (Iso Seq) full length transcripts 14 , and proteins from other species. The gene models were filtered to remove transposons and low confidence predictions.…”
Section: Methodsmentioning
confidence: 99%